Ladies of the lake - Smith, Haywood, 1949- (St. Martin's Press, 2009)
Spending a summer together in the hopes of inheriting their grandmother's lake estate, four sisters share old rivalries and new understandings while struggling with respective challenges in the areas of finance, marriage, and boundaries.